Development of Simulation-based Transmission Line Learning Media: Case Study of GMR-GMD Model on Voltage Regulation and Transmission Line Efficiency - Rahmaniar Rahmaniar; Khairul Khairul; Agus Junaidi; Ihsan Fahreza (AL-ISHLAH: Jurnal Pendidikan, 2025)
The integration of computer-based simulations in electrical engineering education enhances students' understanding of complex concepts such as Geometric Mean Radius (GMR) and Geometric Mean Distance (GMD) in transmission line systems. This study aimed to develop and evaluate a MATLAB-based simulation tool to support learning in voltage regulation and efficiency analysis. Adopting a Research and Development (RD) methodology guided by the ADDIE model, the simulation was tested with 32 electrical engineering students. Expert validation, conducted by three power systems professors and two instructional technology specialists, confirmed high content validity (average score 85%). Data analysis using SmartPLS revealed that simulation quality significantly influenced both conceptual understanding (β = 0.903) and learning effectiveness (β = 0.977), with strong model fit (R² = 0.846). Students’ comprehension of voltage regulation and efficiency improved significantly, as indicated by N-gain scores of 0.75 and 0.72, respectively, while parameter analysis proficiency rose from 42.8% to 80.7%. These findings suggest that the simulation tool not only enhances academic learning but also offers industrial benefits. Specifically, it provides power utilities with a cost-effective means to optimize transmission line designs, reducing iteration costs by up to 60%. It also enables rapid prototyping of conductor configurations and serves as a standardized platform for professional training. Furthermore, the tool supports sustainable energy efforts by improving the integration of renewable energy sources through optimized line parameter analysis.